Severe preoperative pain, functional decline, and high anxiety levels hinder the efficacy of multidisciplinary interventions in patients who underwent primary total knee arthroplasty - Dong-Seok Yang; Young Dae Jeon; Chung-Reen Kim; Sang-Gon Kim; Ki-Bong Park (Journal of Orthopaedic Surgery and Research)
Abstract Background Patients experience clinically significant anxiety from the time they are recommended to undergo total knee arthroplasty (TKA). This study aimed to evaluate the efficacy of a preoperative intervention regarding anxiety levels in patients undergoing TKA for knee osteoarthritis (OA) and to evaluate whether patient characteristics affect the effectiveness of the intervention according to anxiety level. Methods This retrospective observational study recruited 89 patients who underwent TKA under general anesthesia for knee OA. The preoperative multidisciplinary intervention comprised rehabilitation education and an interview with an orthopedic surgeon regarding surgical preparation status. The State-Trait Anxiety Inventory (STAI)-X was administered before and after the preoperative intervention. Patients with baseline clinically meaningful state anxiety (CMSA) status were divided into a group that improved to a non-CMSA status (improved group) and a group that showed no change in CMSA status after the preoperative multidisciplinary intervention (non-improved group). Results The mean STAI-X score significantly decreased from 46.5 points before the preoperative multidisciplinary intervention to 37.4 points after the intervention (P < 0.001). The proportion of patients with CMSA also significantly decreased from 36.0% before the intervention to 14.6% after the intervention (P < 0.001). The preoperative pain scale score was significantly higher in the non-improved group than in the improved group. The Tegner activity level was significantly lower in the non-improved group than in the improved group. The preoperative knee function scores, KSS and WOMAC scores, in the non-improved group were significantly worse than in the improved group. Additionally, the preoperative STAI-X score was significantly higher in the non-improved group than in the improved group. Conclusions For patients undergoing TKA, the implementation of a patient-specific preoperative multidisciplinary intervention, which consists of preoperative rehabilitation education and a surgeon interview, helps reduce preoperative anxiety. However, these preoperative multidisciplinary interventions may not be effective in patients who present with severe pain, poor functional status, or high anxiety levels before surgery.